Stable oxygen and carbon isotope records of coral 18SM-C2, northeast Brazil - Natan S Pereira; Leon J Clarke; Cristiano Mazur Chiessi; Hali Kilbourne; Stefano Crivellari; Francisco William Cruz; Yu Liu; Chuan-Chou Shen; Ruy Kenji P Kikuchi; Barbara Pinheiro; Guilherme Longo; Alcides Sial; et al. (PANGAEA, 2025)
This dataset comprises stable oxygen and carbon isotope records derived from a coral core of the species Siderastrea stellata (labled 18SM-C2), collected from the Maracajaú Reef (5.35°S, 35.24°W) along the northeastern coast of Brazil. A total of 768 isotopic measurements were performed on coral 18SM-C2, with powder samples acquired at a resolution of 0.4 mm, covering a temporal span of 93 years. δ18O and δ13C values were calibrated against the Vienna Pee Dee Belemnite (VPDB) standard using NBS19, with an analytical precision better than ±0.07 for δ18O and ±0.05 extperthousand for δ13C (±1σ, n = 141). Additionally, annual growth rate data for 18SM-C2 are provided, determined by counting density bands visible in X-ray radiograph.